2009
DOI: 10.1152/jn.00116.2009
|View full text |Cite
|
Sign up to set email alerts
|

Motion Perception During Variable-Radius Swing Motion in Darkness

Abstract: Using a variable-radius roll swing motion paradigm, we examined the influence of interaural (y-axis) and dorsoventral (z-axis) force modulation on perceived tilt and translation by measuring perception of horizontal translation, roll tilt, and distance from center of rotation (radius) at 0.45 and 0.8 Hz using standard magnitude estimation techniques (primarily verbal reports) in darkness. Results show that motion perception was significantly influenced by both y- and z-axis forces. During constant radius trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
4
14
1
Order By: Relevance
“…Thus it is essential to train subjects to reduce inter-subject variability and familiarize them with the experimental reporting method. Furthermore, in our earlier study (Rader et al 2009), we confirmed that untrained naïve subjects had much higher reporting variance than trained subjects, though the mean reports were not significantly different without training.…”
Section: Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…Thus it is essential to train subjects to reduce inter-subject variability and familiarize them with the experimental reporting method. Furthermore, in our earlier study (Rader et al 2009), we confirmed that untrained naïve subjects had much higher reporting variance than trained subjects, though the mean reports were not significantly different without training.…”
Section: Methodssupporting
confidence: 78%
“…All subjects provided informed consent. Six subjects (3 male, 3 female) had participated in a previous separate companion experiment (Rader et al 2009) that used similar motion profiles without visual cues. All ten subjects performed three sessions, totalling 36 trials (3×12), for this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations